Soil and above-ground of energy willow and measures to control population - Sabluk, V.; Svidelska, N.; Zmievsky, O.; Dymytrov, V. (Quarantine and plant protection, 2025)
Goal. To determine the species composition of soil and above-ground pests in energy willow plantations, assess population density, and develop measures to control their numbers. Methods. Field, laboratory, and statistical methods. Results. It was established that energy willow plantations are damaged by a complex of soil and above-ground phytophagous pests, which, under plantation cultivation, can cause significant harm to the plants. Soil pests — larvae of May beetles, click beetles, darkling beetles, and wheat beetles — damage the root system by severely gnawing young roots. Among above-ground phytophages, the most dangerous for the plantations are the willow leaf beetle, leaf aphids, willow scale insect, meadow froghopper, and spider mite, which suck sap from leaves, shoots, and stems. Control measures in energy willow plantations include soaking cuttings in solutions of systemic insecticides against soil pests, spraying plants with biological insecticides against above-ground pests, and organizational/management measures against stem-boring species — timely cutting and proper utilization of the above-ground biomass. Conclusions. Energy willow plantations are damaged by many pest species. It is important to know the species composition of the pests and to implement timely control measures using modern plant protection tools, such as systemic insecticide solutions — Dantop 50 WG (clothianidin, 500 g/kg), Cruiser 600 FS (thiamethoxam, 600 g/L), Gaucho 600 FS (imidacloprid, 600 g/L) — and biological preparations Lepidocid-BTU (viable cells of Bacillus thuringiensis var. kurstaki, endospores, and biologically active products of bacterial metabolism: protein crystals — endotoxin, titer not less than 1 × 10⁹ CFU/cm³), Bitoxibacillin-BTU (viable cells of Bacillus thuringiensis var. thuringiensis, endospores not less than 1 × 10⁹ CFU/cm³, protein crystals (endotoxin) and thermostable exotoxin), and Actoverm (a complex of natural avermectins — Aversectin C (0.2%) produced by Streptomyces avermitilis, with high insecticidal and acaricidal activity).